Kampanye Gizi Seimbang Melalui Kesenian Rabab - John Amos (Poltekkes Kemenkes Padang, 2018)
ABSTRACT The prevalence of underweight children under five in Indonesia is still high, compared to the target of Indonesia's MDGs of 18.5% West Sumatra is still below the target. Health problems can not only be solved by the government, but community involvement is required, therefore the potential needs to be mobilized. Rabab is a traditional Minangkabau traditional string instrument made from coconut shell. With this rabab can be channeled one's musical talents. Usually in this rabab narrated a variety of nagari stories or known by the term Kaba.merupakan a traditional theater that is populist in Minangkabau area, West Sumatra. Research with qualitative approach with research strategy